2012
DOI: 10.1542/peds.2012-0541
|View full text |Cite
|
Sign up to set email alerts
|

Management of Neonates With Suspected or Proven Early-Onset Bacterial Sepsis

Abstract: With improved obstetrical management and evidence-based use of intrapartum antimicrobial therapy, early-onset neonatal sepsis is becoming less frequent. However, early-onset sepsis remains one of the most common causes of neonatal morbidity and mortality in the preterm population. The identification of neonates at risk for early-onset sepsis is frequently based on a constellation of perinatal risk factors that are neither sensitive nor specific. Furthermore, diagnostic tests for neonatal sepsis have a poor pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
450
4
25

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(486 citation statements)
references
References 89 publications
7
450
4
25
Order By: Relevance
“…(12,13) During the five years studied, early sepsis of probable maternal origin stood out with the highest frequency (n=35), being cited in other studies as one of the most common diagnoses at the neonatal intensive care unit and probably related to prenatal care defects. (9,13,14) No epidemiological evidence was found in this study or in the literature to support the increased risk of late sepsis after early sepsis in surviving infants when compared to infants without early sepsis, despite the longer hospitalization, need for invasive care procedures to treat the infection and greater risk of death. (15) Among the infants who developed hospital infections, those who only experienced an episode of late sepsis represented n= 6, against n = 8 for infants who developed late sepsis after an episode of early sepsis (developed both -early and late), totaling 14 infants with reported episodes of late sepsis, much lower than the number of early sepsis cases.…”
Section: Discussionmentioning
confidence: 64%
“…(12,13) During the five years studied, early sepsis of probable maternal origin stood out with the highest frequency (n=35), being cited in other studies as one of the most common diagnoses at the neonatal intensive care unit and probably related to prenatal care defects. (9,13,14) No epidemiological evidence was found in this study or in the literature to support the increased risk of late sepsis after early sepsis in surviving infants when compared to infants without early sepsis, despite the longer hospitalization, need for invasive care procedures to treat the infection and greater risk of death. (15) Among the infants who developed hospital infections, those who only experienced an episode of late sepsis represented n= 6, against n = 8 for infants who developed late sepsis after an episode of early sepsis (developed both -early and late), totaling 14 infants with reported episodes of late sepsis, much lower than the number of early sepsis cases.…”
Section: Discussionmentioning
confidence: 64%
“…Our data highlight the need to focus additional efforts on the approach to EOS, which necessitates improvements in existing guidelines that drive practice. [24][25][26] In particular, more accurate identification of those who require antibiotic therapy is greatly needed. Kiser et al 31 demonstrated that application of the Committee on Fetus and Newborn's guidelines for evaluation and treatment of infants exposed to maternal chorioamnionitis 24 resulted in many well-appearing infants with sterile blood cultures being treated with prolonged antibiotic courses, subjected to invasive procedures, and hospitalized for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
“…Non-culture-based tests may be more helpful in identifying neonates who are unlikely to have infection, when culture-based methods are inconclusive. 39 …”
Section: Non-culture-based Diagnosticsmentioning
confidence: 99%
“…47 Overall, neutrophil indices seem to be more helpful for excluding infants without infection than for including infants with infection. 39 …”
Section: Neutrophil Number and Functionmentioning
confidence: 99%
See 1 more Smart Citation